2018
DOI: 10.1002/jcsm.12296
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐23a/27a attenuates muscle atrophy and renal fibrosis through muscle‐kidney crosstalk

Abstract: BackgroundThe treatment of muscle wasting is accompanied by benefits in other organs, possibly resulting from muscle–organ crosstalk. However, how the muscle communicates with these organs is less understood. Two microRNAs (miRs), miR‐23a and miR‐27a, are located together in a gene cluster and regulate proteins that are involved in the atrophy process. MiR‐23a/27a has been shown to reduce muscle wasting and act as an anti‐fibrotic agent. We hypothesized that intramuscular injection of miR‐23a/27a would counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
106
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 49 publications
(112 reference statements)
5
106
0
Order By: Relevance
“…In our earlier publication we treated diabetic mice with a muscle injection of AAV-microRNA and observed that this microRNA was transported from muscle to kidney by exosomes. 27 The current study indicates that kidney fibrosis is reduced when muscle wasting is reduced following treatment using injected exosomes containing miR-29. The downstream kidney benefit suggests that the miR-29 in the injected exosomes is functional.…”
Section: Discussionmentioning
confidence: 63%
“…In our earlier publication we treated diabetic mice with a muscle injection of AAV-microRNA and observed that this microRNA was transported from muscle to kidney by exosomes. 27 The current study indicates that kidney fibrosis is reduced when muscle wasting is reduced following treatment using injected exosomes containing miR-29. The downstream kidney benefit suggests that the miR-29 in the injected exosomes is functional.…”
Section: Discussionmentioning
confidence: 63%
“…7 The related proteins MuRF-2 and MuRF-3 bind to microtubules and are implicated in sarcomere formation with evident functional redundancy, which has proven to be important for the maintenance of skeletal muscle, as double knockout mice lead to myopathy, reduced fore generation, and fibre type shift. 15 Recently, the lncRNA MAR1 has been shown to act as a miR-487b scavenger to regulate Wnt5a protein expression leading to stimulated muscle differentiation and regeneration as well as increased strength in mice 16 making the already complex miR regulatory system even more complicated. 9 In a rat model of paralysed muscle by spinal cord injury, a down-regulation of miRs 23a, 23b, 27b, 145, and 206 was observed 56 days after injury, 10 while injection of 30 μg of mir-206 attenuated muscle loss in a rat denervation model.…”
Section: Introductionmentioning
confidence: 99%
“…14 Overexpression of miR-23a/27a in muscle attenuated diabetes-induced muscle cachexia and attenuates renal fibrosis lesions via muscle-kidney crosstalk in streptozotocin-induced diabetic mice. 15 Recently, the lncRNA MAR1 has been shown to act as a miR-487b scavenger to regulate Wnt5a protein expression leading to stimulated muscle differentiation and regeneration as well as increased strength in mice 16 making the already complex miR regulatory system even more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are a kind of nano-vesicle secreted by cells, which carry a large number of active substances and transmits communication between cells. Renal exosome participates in renal regeneration, repair, and communication between renal tubular cells, regulates the growth of osteocytes, plays a vital role in the progression and control of nephropathy and renal tumor, and has the potential to be used as a targeted therapeutic agent for the renal disease [27,28]. Recent studies have shown that, In UUO mice, tail vein injection of exosome secreted by MSCs overexpressing miRNA-let-7c can alleviate renal injury and down-expression in UUO kidney [29].…”
Section: Discussionmentioning
confidence: 99%